TECHNOLOGIES OF USE OF PETTING AND TOYS GENRES IN THE SPHERE OF ART STUDIES IN THE OPE (British Journal of Global Ecology and Sustainable Development, 2023)
The article focuses on the skills of using scenarios of various genres and art fields in preschool educational organizations.